Personal Competence Profile as a Format of Interaction Between a University Graduate and an Employer in the context of Digitalization of Life - Lyudmila N. DEGTERENKO; Elena A. KONYAEVA; Liliya M. BAZAVLUTSKAYA; Natalya Yu. KORNEEVA; Lyudmila A. KOSTRYUKOVA; Larisa N. PAVLOVA; Olga N. SHVARTSKOP; Natalia A. VASILKOVA (Communications of International Proceedings, 2021)
Modern society is undergoing a digital transformation that affects all spheres of public life: the system of state power, the functioning of state-owned companies and the business environment, education and personality as well. The system of communication of students and graduates of educational organizations with potential employers has also undergone modifications. The study assumes that a personal competency profile should become a new format for their interaction. Revealed and disclosed the content of theoretical and methodological approaches to the definition of the concept of "personal competence profile". The forms of presentation of a personal competence profile are described, to which the authors include an electronic portfolio created in an educational organization, pages on social networks, sites, personal blogs, and a dynamic portfolio.
Keywords: Personal Competence Profile; Digital Transformation; Employer; Graduate Of An Educational Organization; Portfolio; Dynamic Portfolio